(untitled) (Revista de Investigaciones Universidad del Quindío, 2023)
The world currently values the importance of adapting technological tools and web portals (web 2.0) with project management, especially focused on society. Communication plays a fundamental role in society. Social networks have marked a high impact on companies, in their different departments, including the project management office (PMO), an area that must constantly communicate and report what is happening with its portfolio of projects, implementing these new communication strategies generate a great benefit to the interested community (Stakeholders) of a particular project. The objective of this article is to analyze the impact of social networks in the management of social projects.